2022
DOI: 10.1002/jpln.202100233
|View full text |Cite
|
Sign up to set email alerts
|

Detection of calcium phosphate species in soil by confocal μ‐Raman spectroscopy#

Abstract: Background Raman spectroscopy is a promising but largely underexplored tool for the detection of phosphates (P) in soil. Although it requires minimal sample preparation, it has been demonstrated mainly in test matrices or substrates to circumvent the typical signal interference caused by fluorescence of organic matter in actual agricultural soils. Aims The aim of this study was to highlight the Raman spectroscopic detection and identification of distinct calcium phosphate species amended in contrasting soil ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…[ 15,20 ] This finding is in accordance with our previous Raman and SERDS studies on selected soil types where the detection of hydroxyapatite has already been demonstrated. [ 5,12 ] This result is not surprising as all calcium orthophosphates, for example contained within commercial fertilizers, convert to hydroxyapatite in soil over time. [ 9 ] It is important to note that the intense and spectrally broad feature above 1140 cm −1 in the shown SERDS spectrum of hydroxyapatite is not a Raman signal as it does not shift with the shift in excitation wavelength as applied for SERDS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 15,20 ] This finding is in accordance with our previous Raman and SERDS studies on selected soil types where the detection of hydroxyapatite has already been demonstrated. [ 5,12 ] This result is not surprising as all calcium orthophosphates, for example contained within commercial fertilizers, convert to hydroxyapatite in soil over time. [ 9 ] It is important to note that the intense and spectrally broad feature above 1140 cm −1 in the shown SERDS spectrum of hydroxyapatite is not a Raman signal as it does not shift with the shift in excitation wavelength as applied for SERDS.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of micro-Raman spectroscopy with spot sizes on the order of a few micrometers, identification of individual soil constituents is rather easy as for each measurement spot mostly pure component spectra can be acquired. [5,11,12,17] It should be noted that in our study, an excitation and collection spot size of approximately 100 μm has been selected to average out soil spatial heterogeneities on the micrometer scale. The recorded spectra from individual measurement spots will thus very likely contain molecule-specific information from more than a single species in most cases.…”
Section: Influence Of Soil Heterogeneity On Detected Spectramentioning
confidence: 99%
See 3 more Smart Citations